Eastern Philosophies and Psychology: Towards Psychology of Self-Cultivation - Kin-Tung Yit (Frontiers Research Topics, 2017)
The publication of this book, East Asian Philosophies and Psychology: Towards Psychology of Self-cultivation, signifies an important breakthrough for the indigenization movements of psychology which have happened in many non-Western countries since 1980s. Viewing from the perspective of scientific revolution (Kuhn, 1969), when Western paradigms of psychology are transplanted to non-Western countries and encounter anomalies which cannot be explained by the imported theories, the foreign theories are in a state of crisis waiting for scientific revolution.